2015
DOI: 10.1128/jcm.03455-14
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Klebsiella pneumoniae Causing Bloodstream Infections at a New York City Tertiary Care Hospital: Diversification of Multidrug-Resistant Isolates

Abstract: bDespite the growing importance of carbapenem-resistant Klebsiella pneumoniae (CRKP), the clonal relationships between CRKP and antibiotic-susceptible isolates remain unclear. We compared the genetic diversity and clinical features of CRKP, third-generation and/or fourth-generation cephalosporin-resistant (Ceph-R) K. pneumoniae, and susceptible K. pneumoniae isolates causing bloodstream infections at a tertiary care hospital in New York City between January 2012 and July 2013. Drug susceptibilities were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 27 publications
4
63
1
2
Order By: Relevance
“…Exclusion of these patients may also account for the paradoxically lower mortality rates seen in immunosuppressed patients. Although we did not perform molecular testing on all isolates to identify carbapenem resistance mechanisms, two recent studies of CRKP BSI in New York City, both of which included the centers in this study, reported that 94% and 100% of CRKP isolates were KPC producers (29,30). Our molecular testing of a limited number of isolates in this study confirmed these findings.…”
Section: Discussionsupporting
confidence: 77%
“…Exclusion of these patients may also account for the paradoxically lower mortality rates seen in immunosuppressed patients. Although we did not perform molecular testing on all isolates to identify carbapenem resistance mechanisms, two recent studies of CRKP BSI in New York City, both of which included the centers in this study, reported that 94% and 100% of CRKP isolates were KPC producers (29,30). Our molecular testing of a limited number of isolates in this study confirmed these findings.…”
Section: Discussionsupporting
confidence: 77%
“…This is illustrated by the phenotypically heterogeneous K. pneumoniae strains that were isolated repeatedly from the airway and blood over a 3-month period of a nonneutropenic mechanically ventilated patient ( Figure 1A). We used a murine model of pulmonary infection to characterize the innate immune response to ST258 isolate 35 (KP35), a CRKP isolate representative of many strains recovered from our hospital, expressing the most common cps (capsular protein) and wzi (cps component) genotypes (1). Following intranasal delivery of a high inoculum (10 8 CFU) to WT C57BL/6J mice, greater than 10 4 CFU/ml were isolated from the lungs and airways, accompanied by high-grade bacteremia and weight loss over the 96-hour course of infection ( Figure 1, B and C).…”
Section: Resultsmentioning
confidence: 99%
“…We selected the representative clinical isolate KP35 from a patient with bacteremia for comprehensive study (1). It was chosen because it is a common isolate recovered in our institution and it expresses the most common cps and wzi genotypes.…”
Section: Study Isolates and Chart Reviewmentioning
confidence: 99%
“…K antigens have been traditionally assigned by using serological methods (201). Recently, however, K-antigen typing is often performed by sequencing of the wzi locus (206)(207)(208)(209)(210). This locus is present in all capsular types of K. pneumoniae, and different wzi locus sequences are strongly associated with specific K antigens.…”
Section: Capsulementioning
confidence: 99%